Effects of alkali cations and halide anions on the DOPC lipid membrane - Vácha, Robert; Siu, Shirley W I; Petrov, Michal; Böckmann, Rainer A; Barucha-Kraszewska, Justyna; Jurkiewicz, Piotr; Hof, Martin; Berkowitz, Max L; Jungwirth, Pavel (The journal of physical chemistry. A, 2009)
By means of molecular dynamics simulations with an all-atom force field, we investigated the affinities of alkali cations and halide anions for the dioleoylphosphatidylcholine lipid membrane in aqueous salt solutions. In addition, changes in phospholipid lateral diffusion and in headgroup mobility upon adding NaCl were observed using fluorescence spectroscopy. The simulations revealed that sodium is attracted to the headgroup region with its concentration being maximal in the vicinity of the phosphate groups. Potassium and cesium, however, do not preferentially adsorb to the membrane. Similarly, halide anions do not exhibit a strong affinity for the lipid headgroups but merely compensate for the positive charge of the sodium countercations. Nevertheless, larger halides such as bromide and iodide penetrate deeper into the headgroup region toward the boundary with the hydrophobic alkyl chain, this effect being likely underestimated within the present nonpolarizable force field. Addition of alkali halide salts modifies physical properties of the bilayer including the electronic density profiles, the electrostatic potential, and the area per lipid headgroup.
Keywords: Adsorption; adsorpce; alkálie; Phosphatidylcholines; fluorescenční spektrometrie; fosfatidylcholiny; lipidové dvojvrstvy; biologické modely; roztoky; Models, Biological; statická elektřina; chlorid sodný; Spectrometry, Fluorescence; povrchové vlastnosti; Solutions; Lipid Bilayers; Alkalies; Sodium Chloride; počítačová simulace; Hydrocarbons, Halogenated; halogenované uhlovodíky; Surface Properties; Computer Simulation; Static Electricity; kationty; Cations; anionty; Anions